Recovery Economy antara Pemerintah China dan Indonesia Melalui Kerjasama di Sektor Perdagangan dan Investasi Setelah Pandemik - Jessica Ika Samudra (Syntax Idea)
The continuation of the China-Indonesia cooperation that has been forged through the ACFT, as explained earlier, has an influence on friendship in the international arena as well as economic improvement. can be seen in Indonesia's export figures to China, which continue to increase from year to year. The turmoil that has been caused by the Coronavirus Disease-2019 (Covid-19) has weakened all countries internationally and also undermined all sectors, not just health, which was the first trigger for the virus, but also the economic sector, which has implications for the crises of countries in the world. Through the concept of national interest, in which the state must prioritize its interests above all, especially in the four aspects of this concept, the cooperation between the governments of China and Indonesia in the trade and investment sector has produced beneficial results for improving economic stability and the welfare of their respective countries.